Responsible investing - Sherwood, Matthew W., 1983-; Pollard, Julia, 1995- (London : Routledge, 2023)
"Responsible Investing is a holistic resource on Environmental, Social, and Governance (ESG) investing for undergraduate and graduate programs. It provides a thorough background and history of ESG investing, as well as cutting-edge industry developments, introducing the reader to the rapidly evolving field of responsible investing. Building from the first volume, this second edition provides new updates where appropriate as well as new emphasis on the development of standards in terminology and metrics. Opening with the background of ESG investing, the book discusses the development of ESG risks and provides an overview of ESG rating systems. It outlines the current position of ESG investing in portfolio management through granular analysis, provides insight into common investor concerns about ESG investments, presents qualitative theories, and reviews literature modelling ESG investment performance. Finally, the authors provide readers with a foundation on the development of financial models measuring risk and return, which can be used to evaluate the performance of ESG investments. This new edition offers updated statistics and a new chapter on regulation, reporting and taxonomy in ESG investing, as well as new international case studies. Following a summary approach, Responsible Investing is a valuable textbook which provides a context in which upper-level students of ESG investment and sustainable finance can specialise"--
Keywords: Investments -- Social aspects; Portfolio management; BUSINESS & ECONOMICS / Business Ethics; BUSINESS & ECONOMICS / Finance; BUSINESS & ECONOMICS / Investments & Securities